T-shirt. African National Congress (S.A.) - Nursery school - Moses Kotane (in ANC exile project of Mazimbu, Tanzania)
T-shirt. African National Congress (S.A.) - Nursery school - Moses Kotane (in ANC exile project of Mazimbu, Tanzania).